Analisis Faktor-Faktor Penerimaan Simoppeda di Bagian Administrasi Pembangunan Sekretariat Daerah Kabupaten Mukomuko - Daniel Agustian; Fahmi Rizal; Dedy Irfan (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Simoppeda is an information system that provides information services and reporting on the implementation of development activities. In its implementation, the use of Simoppeda is still not optimal and still facing several obstacles. This research is conducted to analyze the factors of user acceptance of Simoppeda implementation in the Development Administration Section of Regional Secretariat of Mukomuko Regency. The purpose of this study is to determine the relationship between perceived ease of use, perceived usefulness, selfefficacy, and facilitating conditions the acceptance of Simoppeda itself. The research employs correlational research method with quantitative approach. The determination of samples is by using saturated sample technique. Instrument validity test is by using corrected item - total correlation technique, while the reliability test used is alpha cronbach. The instrument is in the form of questionnaires. The data analysis technique used is descriptive statistics and nonparametric inferential statistics; Spearman Rank. The result showed that there is a strong and significant correlation between perceived ease of use, perceived usefulness, self-efficacy and facilitating conditions with the acceptance of Simoppeda. These results can be used as guidelines in the development of Simoppeda to pay attention to the factors that underlying the acceptance of Simoppeda.